عالمی قیام ِ امن میں سیرت نبی ﷺ کا کردار: ایک تحقیقاتی مطالعہ: A research study of the Role of Seerat ul Nabi ﷺ in establishing Global Peace - Dr. Muhammad Waqar; Dr. Noman Naeem; Maria (Al Manhal Research Journal, 2025)
Islam is a religion of peace and harmony. It preaches security and safety in society more than anarchy or disorder. Since a safe and sound society is the foundation for the development of an individual, community, and soul, Islam lays down its principles based on the establishment of a social environment wherein peace prevails. Without peace, high aspirations tend to remain unfulfilled dreams. Islam condemns violence. It advocates equality and justice to Muslims and all human beings; it opposes oppression in all forms. It promotes life in harmony with several classes, both Islamic and non-Islamic. The Qur'an portrays the Holy Prophet Muhammad ﷺ as an everlasting and universal messenger, Rahmatul-lil-Alameen (Mercy to all the worlds). His political, economic, social, and governance systems, programs, and teachings sought to end oppression and injustice, preserve human dignity, defend fundamental rights, and end all sources of conflict to bring about world peace. Islam places great importance on human life, believing that the death of one innocent person is the same as the death of all people. Prophet Muhammad ﷺ's life, both before and after he became the Prophet, is a real-life example of tolerance, wisdom, patience, and peace. His actions demonstrated an innate propensity for promoting peace even as a young boy. His foresight, profound wisdom, and admirable morals are timeless examples of contented living. This study will examine what peace means and how the Prophet Muhammad ﷺ fits into the picture of world peace. It will provide insightful information, especially for global organizations that promote human rights and peace.